Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.clml.2017.12.011
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Efficacy of Immunomodulatory-containing Regimens in Relapsed/Refractory Multiple Myeloma: A Network Meta-analysis

Abstract: In patients with RRMM who are suitable for an IMiD-containing regimen, DRd showed clear advantages in survival and response outcomes compared with other IMiD-containing regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 15 publications
1
24
0
Order By: Relevance
“…21 However, establishing efficacy with respect to Ld is insufficient to inform clinical treatment decisions, and the absence of head-to-head trials adds to the complexity of treatment selection among different regimens with a common Ld backbone. 22,23 Although one analysis compared HRs for PFS from all publicly available randomized controlled phase 3 trials, the other analysis described a Bayesian network meta-analysis that compared the clinical efficacy of Ld-containing regimens. 10 ELd showed a relative PFS benefit that was maintained beyond 50 months, and this supports ELd as a feasible treatment regimen for extending survival in patients with RRMM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 However, establishing efficacy with respect to Ld is insufficient to inform clinical treatment decisions, and the absence of head-to-head trials adds to the complexity of treatment selection among different regimens with a common Ld backbone. 22,23 Although one analysis compared HRs for PFS from all publicly available randomized controlled phase 3 trials, the other analysis described a Bayesian network meta-analysis that compared the clinical efficacy of Ld-containing regimens. 10 ELd showed a relative PFS benefit that was maintained beyond 50 months, and this supports ELd as a feasible treatment regimen for extending survival in patients with RRMM.…”
Section: Discussionmentioning
confidence: 99%
“…Although the potential of daratumumab in combination with Ld for long-term durability has yet to be supported by evidence because of the short follow-up, 2 recent network meta-analyses have suggested that DLd may be the best treatment option for patients with RRMM. 22,23 Although one analysis compared HRs for PFS from all publicly available randomized controlled phase 3 trials, the other analysis described a Bayesian network meta-analysis that compared the clinical efficacy of Ld-containing regimens. In our study, instead of using a network meta-analysis to compare treatments, we applied a metric of relative PFS benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Botta et al, in a study of 18 trials, found that DRd ranked first among other salvage regimens per the average value between surface under the cumulative ranking curve of ORR, CR rates, PFS, OS, and safety [50]. Similar conclusions were reached by Dimopoulos et al from analysis of 82 trials comparing IMID-containing regimens [51], and Zhang et al (13 trials that evaluated treatments including, in particular, elotuzumab or daratumumab) [23]. Beurden-Tan et al, in their evaluation of 17 trials, also confirmed DRd as the best available treatment for RRMM [52].…”
Section: Meta-analyses Of Daratumumab Combinationsmentioning
confidence: 63%
“…Meta-analysis of two studies that compared triplet elotuzumab-containing regimens with non-elotuzumab-based combinations concluded that the first regimens were more effective in terms of PFS and ORR [23]. In their network metanalysis of results from the ELOQUENT-2 (Elo-Rd) and POLLUX (DRd) trials, Dimopoulos et al calculated an HR of 0.54 for PFS and 0.82 for OS, indicating that the POLLUX regimen is statistically the most efficacious of the two [51]. This was like the HR value of 0.59 computed for PFS by Maiese et al in their comparison of the same two trials [53].…”
Section: Metanalyses Of Elotuzumab Combinationsmentioning
confidence: 99%
“…Multiple myeloma (MM) is an incurable, debilitating and heterogeneous malignancy that has highly variable clinical course [1][2][3][4][5][6]. It is a plasma cell neoplasm characterized by neoplastic proliferation of a single clone of plasma cells in the bone marrow (BM) producing a monoclonal immunoglobulin and causing anemia, renal failure, bone destruction and infectious complications [7][8][9].…”
Section: Introductionmentioning
confidence: 99%